Tromboembolismo pulmonar suboclusivo en paciente joven a propósito de un caso - Nápoles Lizano, Mario E.; Ramírez Gómez, José I.; Ibáñez Azán, Rafael (CorSalud, 2020)
Tromboembolismo pulmonar suboclusivo en paciente joven a propósito de un caso